2023
DOI: 10.3390/jcm12237442
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide, Procarbazine and Nitrosoureas in the Therapy of Malignant Gliomas: Update of Mechanisms, Drug Resistance and Therapeutic Implications

Bernd Kaina

Abstract: The genotoxic methylating agents temozolomide (TMZ) and procarbazine and the chloroethylating nitrosourea lomustine (CCNU) are part of the standard repertoire in the therapy of malignant gliomas (CNS WHO grade 3 and 4). This review describes the mechanisms of their cytotoxicity and cytostatic activity through apoptosis, necroptosis, drug-induced senescence, and autophagy, interaction of critical damage with radiation-induced lesions, mechanisms of glioblastoma resistance to alkylating agents, including the alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 175 publications
0
8
0
Order By: Relevance
“…Many studies have shown that different mechanisms are involved in TMZ sensitivity or resistance. Various anticancer drugs have been used to increase the sensitivity of cancer cells to TMZ therapy py [ 57 , 58 ]. Oxyphyllanene B can cause TMZ sensitivity by overexpressing PACS2, which can interfere with and impair connection between the endoplasmic reticulum and mitochondria [ 50 ].…”
Section: Temozolomide In Chemotherapy: From History To Molecular Mech...mentioning
confidence: 99%
“…Many studies have shown that different mechanisms are involved in TMZ sensitivity or resistance. Various anticancer drugs have been used to increase the sensitivity of cancer cells to TMZ therapy py [ 57 , 58 ]. Oxyphyllanene B can cause TMZ sensitivity by overexpressing PACS2, which can interfere with and impair connection between the endoplasmic reticulum and mitochondria [ 50 ].…”
Section: Temozolomide In Chemotherapy: From History To Molecular Mech...mentioning
confidence: 99%
“…TMZ is, in clinical use, part of the standard of care for the chemoradiation treatment of glioblastoma (GBM). Its primary cytotoxic mode of action is methylation of the O6-position of guanine, which results in DNA double-strand breaks and subsequent apoptosis [ 28 ]. However, this process does not work in cells that express the DNA repair protein O6-methylguanine-DNA methyltransferase (MGMT), because MGMT is able to effectively remove the methyl group from the O6-position of guanine, thereby disposing of the toxic lesion and providing chemoresistance [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gliom present a more alkaline environment compared to surrounding healthy brain cells, le ing to drug activation [1,3,4,7,8] almost exclusively in the tumor cells [1,7,8,13,14]. Mor ver, senescence induced by TMZ is another phenomenon that should also be mention TMZ senescent GB cells overexpress NF-kB and lead to inflammatory cytokines' prod tion, such as IL6 and IL8; thus, these cells seem not to be eliminated after TMZ and rad therapy and tend to be present even in recurrence of the tumor, with a not yet fully cla fied role [15]. Due to the highly heterogeneous and mutation-prone nature of GB, resistance to TMZ is developed and accounts for over 50% of GB patients that eventually fail to respond to the therapy [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, senescence induced by TMZ is another phenomenon that should also be mentioned. TMZ senescent GB cells overexpress NF-kB and lead to inflammatory cytokines’ production, such as IL6 and IL8; thus, these cells seem not to be eliminated after TMZ and radiotherapy and tend to be present even in recurrence of the tumor, with a not yet fully clarified role [ 15 ].…”
Section: Introductionmentioning
confidence: 99%